2011
DOI: 10.1111/j.1468-5973.2011.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Steadily Increasing Control: The Professionalization of Mass Death

Abstract: Recent mass death incidents in Japan and Haiti have again focused attention on the challenge of dealing with large numbers of dead. Focusing on mass death incidents involving large numbers of Canadian victims, including the Titanic, Halifax explosion, Air India bombing and the 2004 Tsunami, the paper researches incidents dating back to the beginning of the 20th Century. By examining each stage of the process including initial response, identification, funerals, communication, religious services and inquests, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…The Titanic is also related to later mass casualty disasters. Visual identification methods like those developed after the Titanic continue to be used alongside, or even instead of, forensic identification through, for example, fingerprints and DNA ( Scanlon et al, 2011 ; Scanlon and Hunsberger, 2011 ; Stoney et al, 2011 ). In addition, the identification methods developed by the embalmer in Halifax, John Henry Barnstead – apparently in concert with John R Snow, Jr, the embalmer who traveled aboard the Mackay-Bennett – were applied and further developed in subsequent disasters such as the 1917 Halifax explosion.…”
Section: The Titanic and The History Of Forensic Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The Titanic is also related to later mass casualty disasters. Visual identification methods like those developed after the Titanic continue to be used alongside, or even instead of, forensic identification through, for example, fingerprints and DNA ( Scanlon et al, 2011 ; Scanlon and Hunsberger, 2011 ; Stoney et al, 2011 ). In addition, the identification methods developed by the embalmer in Halifax, John Henry Barnstead – apparently in concert with John R Snow, Jr, the embalmer who traveled aboard the Mackay-Bennett – were applied and further developed in subsequent disasters such as the 1917 Halifax explosion.…”
Section: The Titanic and The History Of Forensic Pmentioning
confidence: 99%
“…In addition, the identification methods developed by the embalmer in Halifax, John Henry Barnstead – apparently in concert with John R Snow, Jr, the embalmer who traveled aboard the Mackay-Bennett – were applied and further developed in subsequent disasters such as the 1917 Halifax explosion. As such, the Titanic recovery played a role in future practices of forensic identification, which only began to be standardized much later, beginning after World War II ( Scanlon, 1998 ; Stoney et al, 2011 ; University of Virginia, 2007 ). 2…”
Section: The Titanic and The History Of Forensic Pmentioning
confidence: 99%
“…Third, the nature of disasters can compound distress. Relatives today expect the dead to be recovered, identified, and treated respectfully (Stoney at al., 2011). Yet, bodies may be irrecoverable, destroyed, or damaged.…”
Section: Primary Challenges: Location Scale and Nature Of Incidentsmentioning
confidence: 99%
“…It appears that existing research was done after significant changes had occurred. The only publication that describes how bodies were dealt with before this research was conducted appears to be a study that covered more than a century of mass death situations in Canada and mass death situations outside of Canada that involved at least 20 Canadians (Stoney, Scanlon, Kramar, Peckmann, Brown, Cormier, & van Haastert, ). That review found that until about the middle of the 20th century, identification of the dead after a mass death incident was fairly informal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, no matter how bodies are identified, there has been steadily increasing control of the identification process. The handling of large numbers of dead – like many aspects of society – has become a controlled affair managed by professionals (Stoney et al., )…”
Section: Literature Reviewmentioning
confidence: 99%